PENGARUH INDEPENDENSI DAN PROFESIONALISME TERHADAP KETEPATAN PEMBERIAN OPINI AUDIT OLEH AUDITOR PADA KANTOR AKUNTAN PUBLIK (KAP) DI KOTA BANDUNG - Muhammad Rizal Satria; Hariyanto Hariyanto; Alvira Isnaeni Nursholikhah (LAND JOURNAL, 2026)
Cases of inaccurate audit opinions by auditors, which have occurred in both government and private institutions and have been published online, demonstrate the weakness of an auditor's independence and professionalism. This research seeks to assess if the independence and professionalism of an auditor influences the accuracy of his or her audit opinions. A quantitative method is utilized in this study and is grounded on the gathering of original information via surveys. The research involved an overall sample of 87 auditors working at twenty public accounting firms (KAP) in Bandung. Data analysis was conducted with SPSS through the application of validity assessments, reliability assessments, normality assessments, multicollinearity assessments, heteroscedasticity assessments, correlation evaluations, multivariate linear regression evaluations, partial t-statistical, simultaneous F-test and study of the R² coefficients. The conclusion of t-value hypothesis test revealed that the variables independence and professionalism each influence the accuracy of auditors' opinions at audit firms (KAP) in Bandung. Likewise, the F-test revealed that independence and professionalism simultaneously influence the accuracy of auditors' opinions at audit firms (KAP) in Bandung.